The Impact of science and innovation to improve the teaching-learning process - Antonio Jesus Perez Sierra; Antonio Jesus Perez Sierra; Ana Erika Gutierrez Valdez; Alberto Bautista Sanchez Oms; Alberto Miguel Morales Fabregas; Yanet Parrera Herrera (Universitas Pendidikan Ganesha, 2022)
When we talk about science and innovation, it is to refer to the main support of human activity, to transform the objective reality of the teaching contexts, the theoretical and empirical methods, allow us the logical reasoning of the processes and phenomena, to give answers to possible hypotheses, and make decisions and advance in thinking, cultural, artistic, social, and educational, as the basis of analytical, reflective and holistic instruction, according to its impact on the educational field. This study aims to know the impact that science and innovation have had on students of Physical Culture to improve the teaching-learning process. To achieve this, the research starts from a qualitative approach, based on a descriptive and longitudinal study. Different methods and instruments were used, such as the documentary review, the questionnaire, the survey, and the triangulation. In addition, the criterion of inclusion and exclusion. The most relevant findings contribute to linking the components (objectives, contents, and methods) with science and innovation to improve the teaching-learning process. In conclusion, pedagogical interventions provide solutions to teaching work as a significant means for teaching science and innovation.